Doing quantitative research in education with SPSS - Muijs, Daniel (SAGE, 2004)
This book provides an introduction to using quantitative methods in educational research. The author writes for non-mathematical students, avoiding the use of mathematical formulae wherever possible. No prior knowledge of quantitative methods is needed to use this book.